THE EFFECTIVENESS OF USING VARIOUS PLAY METHODS TO ENHANCE COGNITIVE DEVELOPMENT IN EARLY CHILDHOOD: A CRITICAL ANALYSIS AND LITERATURE REVIEW - Suhaini (Formad English Foundation NTB Jakarta, 2024)
This study investigates the effectiveness of various play methods in enhancing children's cognitive development in early childhood education. This study used a qualitative literature review to evaluate the effectiveness of play methods in enhancing cognitive development in early childhood education. Data were gathered from peer-reviewed sources focused on children aged 2-6 years, using systematic checklists to categorize studies. Thematic analysis identified cognitive benefits across play types such as role-playing, puzzles, and educational technology. The findings highlight the most effective play methods for cognitive development. Data were sourced from databases like Google Scholar, JSTOR, and ERIC. The results reveal that engaging children in structured play activities, such as using number cards and puzzles, significantly improved their cognitive abilities, with some methods achieving up to 100% completion in cognitive learning outcomes. Conversely, activities like playing with Lego showed no significant improvement in symbolic thinking for children aged 4-5. Overall, the findings suggest that different play methods contribute variably to cognitive development, with certain approaches yielding higher outcomes, especially in tasks related to numeracy and problem-solving. The study concludes that educational games and interactive play can enhance cognitive skills in early childhood, but effectiveness may vary based on the type of play and age group. These findings provide valuable insights into designing educational play activities that cater to different cognitive needs. Future research should explore the long-term effects of these play strategies and their adaptability across diverse educational settings.